Patriarchal politics, online violence and silenced voices: The decline of women in politics in Zimbabwe (The Strategic Review for Southern Africa, 2023)
In this year's elections in Zimbabwe, the number of women nominated and elected to national office decreased. This decline can be attributed to increased online harassment of women in politics, as well as financial obstacles and patriarchal attitudes. To reverse this trend, it is crucial for the government, political parties and civil society to address gender-based electoral violence effectively. Additionally, the government should genuinely implement gender quotas, focusing on empowering women in politics rather than using quota as a means to improve their international image, attract international donor funds and secure more women voters.